The Problematics of Gender for Aviation Emergency Communication during an Inflight Emergency: A Case Study - Garcia, Angela Cora (Qualitative Sociology Review, 2023)
Due to the rarity of female pilots, aviation communication is typically conducted in a single-gender environment. The role of gender in interactions during inflight emergencies has not yet been adequately explored. This single case analysis uses a qualitative approach based on conversation analytic transcripts to investigate how gender may be relevant either explicitly or implicitly in radio transmissions between flight crew and Air Traffic Control (ATC) personnel, as well as internal ATC phone interactions as participants work to handle an inflight emergency. This incident involved a female pilot and a male copilot, thus providing a naturally occurring rare event to explore the potential relevance of gender. The analysis shows that explicit references to gender are limited to occasional asymmetrical use of gendered address terms and gendered pronouns. Participants also used interactional formulations that—while not explicitly gendered—have been associated in previous research with gender differences in interaction, for example, the use of indirect forms of requests or complaints, actions that imply inferences about the emotional state of participants, or possible confusion over the identity of the pilot given the transitions between male and female sounding voices speaking on behalf of the plane. The findings are discussed in terms of implications for how gender differences can impact aviation communication during emergency incidents.